Incidence of diabetes and ischemic heart disease in COVID-19 post pandemic - Singh, Amrendra Kumar; Choudhary, Raj Kamal; Ragini, Kumari; Perwez, Anjum (International Journal of Research in Medical Sciences, 2023)
Background: The long-term effects of COVID-19 pandemic are currently getting more attention. The majority of individuals with COVID-19 report having symptoms for longer than 4 weeks following their initial appearance. after COVID-19 infection, there is worry that cardiovascular conditions and metabolic conditions may be harmed. Aim of the study the incidence of ischaemic heart disease and diabetes mellitus (DM) post COVID 19 pandemic. Methods: Information for all individuals diagnosed as suffering of COVID-19 were taken at the beginning of the investigation from the health department’s release of electronic medical records in February 2021. The main outcomes analysed were first ever documented cardiovascular disorders (CVD) as well as DM diagnoses. The data were then combined for the time periods following the index date (long COVID-19), for five to twelve weeks following the index date (post-acute COVID19), for four weeks after the date of indexing (acute COVID-19), prior to the index date (Pre-index). For COVID-19 patients as well as control subjects, incidence rates with precise Poisson confidence intervals (CIs) were computed. Results: CVD events was 1362 in COVID-19 study group while it was 131 in control study group at phase corresponding to four weeks after the indexed date. CVD events was 781 in COVID-19 study group while it was 298 in control study group at phase corresponding to five to twelve weeks since the date of indexing. CVD events was 781 in COVID-19 study group while it was 298 in control study group at phase corresponding to five to twelve weeks since the date of indexing. CVD events was 2,134 in COVID-19 study group while it was 298 in control study group at phase corresponding to 13 to 52 weeks since the date of indexing. Conclusions: Early on after COVID-19 infection, the risk of CVD is elevated, and this risk is elevated for up to three months. However, there does not appear to be a long-term rise in the prevalence of CVD or DM in COVID-19 patients who do not already have these illnesses. This study shows that after COVID-19 infection, the incidence of DM is high for at minimum 12 weeks before it starts to decline.